Technical considerations for the generation of novel pseudotyped viruses. (January 2016) - King, Barnabas; Temperton, Nigel J; Grehan, Keith; Scott, Simon D; Wright, Edward; Tarr, Alexander W; Daly, Janet M
A pseudotyped virus (PV) is a virus particle with an envelope protein originating from a different virus. The ability to dictate which envelope proteins are expressed on the surface has made pseudotyping an important tool for basic virological studies such as determining the cellular targets of the envelope protein of the virus as well as identification of potential antiviral compounds and measuring specific antibody responses. In this review, we describe the common methodologies employed to generate PVs, with a focus on approaches to improve the efficacy of PV generation.